2002
DOI: 10.1095/biolreprod66.5.1477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooling and Warming Rate to and from −70°C, and Effect of Further Cooling from −70 to −196°C on the Motility of Mouse Spermatozoa1

Abstract: We have previously reported high survival in mouse sperm frozen at 21 degrees C/min to -70 degrees C in a solution containing 18% raffinose in 0.25 x PBS (400 mOsm) and then warmed rapidly at approximately 2000 degrees C/min, especially under lowered oxygen tensions induced by Oxyrase, a bacterial membrane preparation. The best survival rates were obtained in the absence of glycerol. The first concern of the present study was to determine the effects of the cooling rate on the survival of sperm suspended in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…By varying the position of the cryotube relative to the surface of the LN 2 and the volume of sperm suspension, we found that the survival of spermatozoa in cryotubes was improved to a level similar to that observed in spermatozoa frozen in plastic straws. Previous studies on the cryopreservation of mouse spermatozoa have reported optimal cooling rates of 27-130 [29] or 39-114 C/min [30]. These data are consistent with ours because the cooling rate in our experiments was -143.4 C/ min in cryotubes, although there was a shoulder at around -10 C (Fig.…”
Section: Figsupporting
confidence: 92%
“…By varying the position of the cryotube relative to the surface of the LN 2 and the volume of sperm suspension, we found that the survival of spermatozoa in cryotubes was improved to a level similar to that observed in spermatozoa frozen in plastic straws. Previous studies on the cryopreservation of mouse spermatozoa have reported optimal cooling rates of 27-130 [29] or 39-114 C/min [30]. These data are consistent with ours because the cooling rate in our experiments was -143.4 C/ min in cryotubes, although there was a shoulder at around -10 C (Fig.…”
Section: Figsupporting
confidence: 92%
“…To date, publications dedicated to this topic are rare (Nawroth, et al, 2002;Koshimoto & Mazur, 2002;Isachenko et al, 2004aIsachenko et al, , b, 2008. Recent work has reversed this situation in that favorable results have been obtained in human spermatozoa after excluding permeable cryoprotectants from cryopreservation solutions, increasing the cooling rate and using carbohydrates, proteins and other extracellular agents, to increase the viscosity of the surrounding medium of cells and prevent the formation of any intra-and big extracellular crystals (Isachenko et al, 2004a, b).…”
Section: What Is the Reason?mentioning
confidence: 99%
“…In general, the inclusion of osmotically active, non-permeating compounds into the vitrification solution leads to additional rehydration of cells and, as a result, to decreasing toxic effects of the permeable cryoprotectants on intracellular structures. The non-permeable cryoprotectant sugars possess a unique property: stabilization of a cell membrane (Nakagata & Takeshima, 1992Koshimoto et al, 2000;Koshimoto & Mazur, 2002).…”
Section: What Is the Reason?mentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic effect of the CPA and freezing medium on nonhuman primate sperm cryopreservation may also explain the low efficiency of cryopreservation of nonhuman primate sperm. Studies have indicated that the highest survival rate can be obtained by freezing sperm at their optimal freezing rate [9,22]. In the present study, four freezing rates determined by the distances between cryostraws with sperm and the LN 2 surface were chosen to determine the optimal freezing rate for rhesus macaque sperm cryopreservation.…”
Section: Discussionmentioning
confidence: 99%